Morphological Structure and Anatomy of Bamboo Ampel (Bambusa Vulgaris) in Imogiri - Estikomah; Widodo (Proceeding International Conference on Science and Engineering, 2021)
Abstract. This research aims to find out the morphological structure of bamboo ampel ( Bambusa vulgaris) and the anatomy of bamboo ampel rods (Bambusa vulgaris). This research through two stages, the first stage is exploration and the second stage is the observation conducted in the integrated laboratory of UIN Sunan Kalijaga Yogyakarta. This study produced data in the form of morphological structures namely, the part of the stem that is smooth green shiny, bamboo shoots are fresh green, reeds with triangular tips and bald bases and covered with brown to blackish fur, and the surface of the upper leaves is smooth and shiny, and the lower leaves are fluffy. For its anatomical structure, ampel bamboo has anatomical parts such as the epidermis, cortex, transporting beams (protoxilem, metaxilem, and xilem), as well as fibers. This ampel bamboo transporter file is included in the type III transport file. For bamboo stem components this bamboo ampel is lignin 28.01%, cellulose 44.79%, starch 21.35%, water 6.81%, ash 2.47%, and silica 0.47%.